A new species of the Achalinus rufescens complex (Xenodermidae: Achalinus) from Fujian Province, China - Li, Ke; Wu, Ya-Yong; Xu, Rui-Ying; Zhu, Fei; Ren, Jin-Long; Guo, Peng; Dong, Bing-Jun (Zootaxa, 2021)
A new species of the xenodermid snake genus Achalinus Peters, 1869 is described from Fujian Province, China, based on six specimens. Bayesian inference and maximum likelihood analyses based on a mitochondrial DNA fragment (CO1) indicated the new taxon is different from its congeners (p–distance ≥ 18.5%). Morphologically, the new species can be diagnosed from the other species by a combination of following characters: (1) dorsal scales 23 rows throughout, strongly keeled, the most outer rows on both sides also keeled and slightly enlarged; (2) tail relatively longer, TaL/TL ratio 0.26–0.29 in males, 0.21–0.22 in females; (3) maxillary teeth 30–33; (4) length of suture between internasals significantly longer than that between prefrontals; (5) nasal divided into two sections by nasal cleft; (6) a single loreal; (7) SPO 1, seldom 2; (8) SPL 6, the fourth and fifth contacting eye; (9) IFL5, rarely 6, the first three touching the first pair of chin shields; (10) TMP 7–9, arranged in three rows; (11) VS 142–149 in males, VS 152–154 in females; (12) SC 74–81 in males, SC 63–65 in females, arranged in a single row; (13) cloacal entire; (14) greyish brown above, pale yellow beneath; (15) dorsum with an indistinct longitudinal vertebral stripe. The description of the new species brings the total species of Achalinus to 19.